Scope disambiguation by ellipsis and focus without scope economy - Rooth, Mats (Proceedings of the Amsterdam Colloquium, 2005)
This paper reconstructs the analysis in Danny Fox’s Economy and Semantic Interpretation of ellipsis/focus scope disambiguation effects in a way which eliminates reference to scope economy, instead relying only on focus theory to constrain representations.